2016
DOI: 10.7841/ksbbj.2016.31.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Inhibitory Activity of Lactobacillus plantarum MG989 and Lactobacillus fermentum MG901 Isolated from Vaginal Microbiota of Korean Women against Gardnerella vaginalis and Candida albicans

Abstract: Vaginitis, also known as vaginal infection and vulvovaginitis, is an inflammation of the vagina and possibly vulva. The three main kinds of vaginitis are bacterial vaginosis, vaginal candidiasis, and trichomoniasis. The purpose of this study was to characterize Lactobacillus plantarum MG989 and L. fermentum MG901 isolated from the vaginas of healthy Korean women in terms of their inhibitory activity against the vaginitis associated pathogens such as Gardnerella vaginalis and Candida albicans. Co-culture experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Our previous in vivo studies demonstrated that five lactobacilli strains (Lacticaseibacillus paracasei MG4272, L. rhamnosus MG4288, Ligilactobacillus salivarius MG242, L. fermentum MG901, and Lactiplantibacillus plantarum MG989) isolated from the vaginal tract of healthy Korean women have good probiotic properties, such as acid/bile salt-resistance and adhesion (auto-aggregation). Furthermore, these strains demonstrated potential antimicrobial activity against GV or Candida albicans [14][15][16][17][18], and a three-strain mixture (MG242, MG901, and MG989) exhibited anti-BV activity in GV-infected mice [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous in vivo studies demonstrated that five lactobacilli strains (Lacticaseibacillus paracasei MG4272, L. rhamnosus MG4288, Ligilactobacillus salivarius MG242, L. fermentum MG901, and Lactiplantibacillus plantarum MG989) isolated from the vaginal tract of healthy Korean women have good probiotic properties, such as acid/bile salt-resistance and adhesion (auto-aggregation). Furthermore, these strains demonstrated potential antimicrobial activity against GV or Candida albicans [14][15][16][17][18], and a three-strain mixture (MG242, MG901, and MG989) exhibited anti-BV activity in GV-infected mice [19].…”
Section: Introductionmentioning
confidence: 99%